Conversion of 1,3thiazolidine and its sulfoxide to dihydro1,4thiazine - 한호규; 남기달; W. S. Lee; He Duck Mah (WILEY, 1993)
Two methods for constructing dihydro1,4thiazine 4 were described. 1,3Thiazolidines 5 were converted to dihydro1,4thiazines 4 by chlorinolysis through the unisolable chlorosulfonium salt 10 and sulfenyl chloride 11. Oxidation of the sulfides 5 gave a mixture of pairs of diasteromers 6. In the presence of acid catalyst, both sulfoxides were converted to dihydrothiazine 4 through sulfenic acid 22. In this reaction the stepwise ring opening involving carbocation 23 seems more probable. The structures of 4 were proven by the independent synthesis involving 3bromo2oxobutanoic acid derivatives. Copyright ？ 1993 Journal of Heterocyclic Chemistry